Postoperative Delirium Following Orthognathic Surgery in a Young Patient - Costa, Fernanda Herrera da [UNESP]; Herrera, Paulo Adilson; Pereira-Stabile, Cecilia Luiz; Vitti Stabile, Glaykon Alex (Elsevier B.V., 2017)
Delirium is an organic mental syndrome with acute onset characterized by diffuse brain dysfunction and neural activity disorganization. It is usually related to cognition and perception changes, decreased level of consciousness, and disorganization of thoughts that are unrelated to previous dementia. Occurrence is more frequent in patients with previous degenerative disease and elderly patients, especially those older than 85 years. Although the pathophysiology is not totally known, studies have shown that, among the main factors that lead to delirium, the drugs used for general anesthesia induction are the most relevant (hypnotics, anticholinergic drugs, and H-2 receptor blockers), especially those used in long surgical procedures. This report describes the case of a 24-year-old woman with a noncontributory medical and psychological history. She underwent bimaxillary orthognathic surgery with a total general anesthesia time of 7 hours. Postoperatively, she developed agitation, confusion, and delirium. After a psychiatry consult and discussion with the anesthesia team, the diagnosis of psychotic break owing to late postoperative delirium was established. (C) 2016 Published by Elsevier Inc on behalf of the American Association of Oral and Maxillofacial Surgeons